Regular, low-dose methadone for reducing breathlessness in people experiencing or at risk of neurotoxic effects from morphine: A single-center case series - Sobanski, Piotr Z.; Currow, David C. (Frontiers in Medicine, 2022)
Breathlessness is common symptom suffered by people living with advanced malignant and non-malignant disease, significantly limiting their quality of life. If it emerges at minimal exertion, despite maximal, guidelines-directed, disease-specific therapies, it should be considered persistent and obliges to symptomatic treatment. Opioids are recommended for symptomatic treatment of persistent breathlessness, with morphine most studied for this indication. It is extensively metabolized in liver into water-soluble 3- and 6-glucuronides, excreted by the kidneys. In case of advanced renal failure, glucuronides accumulate, mainly responsible for the toxicity 3-glucuronides. Some people, predominantly those with advanced renal failure, develop neurotoxic effects after chronic morphine, even prescribed at very low-dose. A single-center case series of consecutive patients experiencing neurotoxic effects after long-term, low-dose morphine, or at risk of such effects, were transferred to methadone to avoid the accumulation of neurotoxic metabolites. Over 4.5years 26 patients have been treated with methadone in median dose 3.0mg/24h p.o, for persisting breathlessness. 16 treated previously with opioids (usually morphine,, median dose 7.0mg/24h p.o.) were transferred to methadone, with median dose 3.0mg/24h p.o., median morphine to methadone dose-ratio was 2.5:1. All patients experienced meaningful improvement in breathlessness intensity after methadone by median 5 points (range 1-8) on the 0-10 numerical rating scale (NRS) in the whole group vs pretreatment, and further improvement by median 2 points (range 0-8) in those treated mainly with morphine. Low-dose methadone can be an efficient alternative to morphine for reducing breathlessness in people experiencing neurotoxic effects, or at risk of them, following treatment with morphine.